Knowledge and Practice of Antenatal Care Among Pregnant Women Attending Rajshahi Medical College Hospital, Rajshahi, Bangladesh: A Cross-Sectional Study - Shahinur Islam (International Journal of Public Health and Nursing, 2026)
Antenatal care (ANC) plays a important role to increased maternal and neonatal health outcomes. Although it is recognized as one of the crucial effective maternal health interventions and the utilization of recommended ANC services in Bangladesh remains suboptimal. According to national data, only 41% of pregnant women were finished four antenatal care visits in 2022. Looking women’s knowledge and self-care practices is essential for strengthening maternal healthcare services. This study focused to evaluate the knowledge and self-care practices related to antenatal care among pregnant women attending at Rajshahi Medical College Hospital (RMCH), examine the association between knowledge and practice and determine the sociodemographic factors enhancing these outcomes. A descriptive cross-sectional study was carried out among 100 pregnant women attending the outpatient department of RMCH. Participants were recruited by using convenience sampling. Data were be collected through a structured interviewer-administered questionnaire that included sociodemographic characteristics, a 20-item knowledge scale and a 25-item self-care practice scale. Data were analyzed by using multiple methods Such as SPSS descriptive statistics, Pearson’s correlation, chi-square test, one-way ANOVA and multiple linear regression. The findings showed that 96.0% of the participants had good knowledge and 86.0% showed good antenatal care practices, in where poor knowledge and poor practice were observed in 4.0% of respondents each. Knowledge scores were positively associated with practice scores (r = 0.732, p < 0.01). Age and educational level were significantly related to both knowledge and practice (p < 0.05), while occupation and monthly family income were not significantly associated. Regression analysis shows that age and occupation essentially predicted knowledge scores, whereas age, education, and occupation were significant predictors of practice scores, accounting for 16.2% of the variation in practice. Foremost, pregnant women attending RMCH showed satisfactory knowledge and self-care practices regarding at antenatal care. On the other hand, deficiencies remained in early first-trimester ANC registration, awareness of pre-eclampsia and regular follow-up visits. Targeted health education and counseling for women with lower educational qualification and younger age groups, together with strengthened community-based maternal health promotion, may further improve ANC utilization in accordance with WHO recommendations.